Antimicrobial sesquiterpene lactones from Artemisia sieberi. Issue 11 (2nd November 2017) - Mohamed, Tarik A.; Hegazy, Mohamed-Elamir F.; Abd El Aty, Abeer A.; Ghabbour, Hazem A.; Alsaid, Mansour S.; Shahat, Abdelaaty A.; Paré, Paul W.
Abstract: Two new sesquiterpene lactones 3 R, 8 R -dihydroxygermacr-4(15), 9(10)-dien-6 S, 7 S, 11 R H, 12, 6-olide (1 ) and 1 R, 8 S -dihydroxy-11 R, 13-dihydrobalchanin(2 ), together with two known compounds 11-epiartapshin (3 ) and 3′-hydroxygenkwanin (4 ), were isolated from Artemisia sieberi . Their structures were elucidated by 1D, 2D NMR, MS, and X-ray diffraction. Compound4 inhibited Gram-positive bacteria Bacillus subtilis and Staphylococcus aureus with Minimal inhibitory concentration values of 50 and 25 μg/disk, respectively. All the isolated compounds exhibited moderate antifungal activities. Abstract :